Development of Accrual-Based Accounting Information System for Financial Planning - Muslimin B; Budi Racmadhani (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2026)
The increasing complexity of financial management in small and medium-sized enterprises (SMEs) requires the implementation of robust accounting systems. While accrual accounting provides more accurate financial insights by recognizing revenues and expenses when incurred, many SMEs still rely on cash-based accounting, hindering their financial decision-making. This research aims to develop an accrual-based accounting information system tailored for SMEs, integrating essential features such as cost control and forecasting. The proposed system automates key processes, from transaction entry to report generation, offering a comprehensive solution to enhance financial transparency and decision-making. The system is evaluated through real-world data simulations to assess its effectiveness in improving reporting accuracy and forecasting capabilities. The results demonstrate that the system improves financial planning and resource allocation, providing valuable insights for SMEs. Future work will focus on scaling the system for larger enterprises and incorporating machine learning techniques to improve financial forecasting and anomaly detection.